Effecting of Teacher Certification on Teacher Performance in Public High Schools: Bibliometrics and Quantitative Analysis - Armin Armin; Amaluddin Amaluddin; Elihami Elihami (Universitas Muhammadiyah Enrekang, 2021)
This study aimed to determine the effect of educator certification on the performance and professionalism of PAI Teachers at State High Schools in Enrekang Regency. The research method is a descriptive-analytic descriptive method to see the effect between the independent and dependent variables. This research is survey research. The population is all PAI teachers of State Senior High Schools in Enrekang Regency who are already certified. The proportional stratified technique does sampling. Determination of the sample using accidental sampling. Data collection techniques used were questionnaire, interview, observation and documentation. Data analysis using descriptive analysis and inferential statistics using the SPSS 22 program. The study results showed that PAI teachers of State Senior High Schools in Enrekang District who were already certified thought that certification was quite decisive in increasing teacher performance. Their level of performance is in a good category, so the proposed hypothesis turns out to be proven. The research implies that the Educational Personnel Education Institution (LPTK) as the certification implementer needs to review the training system used so far, such as the allocation of time, more practical training methods, the determination of resource persons for training facilities and infrastructure. The PAI teachers of the State High School in Enrekang are expected to be more creative in improving performance because the provision of educator certificates only supports more self-improvement.